Economic complexity - Barnett, William A.; Deissenberg, Christophe; Feichtinger, Gustav, 1940- (Elsevier, 2004)
The last fifteen or twenty years have been marked by fundamental advances in the sources of complex behavior in micro- and macro-economics, in the practical and methodological implications of such behavior, and in the methods and tools appropriate to cope with them. Much of these developments have been driven by the recognition and acceptance by economists of approaches initiated in other fields - such as non-linear dynamics, statistical physics, network theory, biology, computer science, and the use of computational methods as problem-solving tools - giving rise to important and innovative impulses to economic thinking. The sixteen papers in this book -- the fourteenth volume in the series International Symposia in Economic Theory and Econometrics - reflect from various perspectives this recent evolution. They are the outgrow from a selection of communications presented at the COMPLEXITY2000 workshop held in Aix en Provence, France, 4-6 May 2000 - a workshop that brought together, from twenty-two nations, almost seventy economists, mathematicians, biologists and physicists interested in complex phenomena. All papers were strictly refereed in the intended tradition of the series: to provide journal quality collections of research papers of unusual importance in areas of currently highly visible activity within the economics profession. With its selection of articles, the book presents an overview of advanced contributions to complexity in economics and social system, such as chaotic dynamics and multiple equilibria, agent-based models, applications of genetic algorithms, non-equilibrium macro-dynamics, information transmission, learning mechanisms. Although the papers address economic problems, the authorship and the perspectives presented are interdisciplinary and provide therefore a number of innovative insights and solutions to classical or new questions.
"Selection of communications presented at the COMPLEXITY2000 workshop held in Aix en Provence, France, 4-6 May 2000"--Foreword.
Keywords: Economics, Mathematical -- Congresses.; Computational complexity -- Congresses.; elektronické knihy; electronic books